Positive effects of sequential air ventilation on cooked hard Graviera cheese ripening in an industrial ripening room. (April 2018) - Corrieu, G.; Perret, B.; Kakouri, A.; Pappas, D.; Samelis, J.
Abstract: An industrial ripening room used for Graviera cheese ripening was equipped in order to compare Continuous Ventilation (CV: full time air circulation) and Temperature based Sequential Ventilation (TSV) processes. Under controlled temperature and Relative Humidity of the ripening room, three reference 30-day ripening trials performed in CV mode were compared to three similar trials performed in TSV mode. TSV was monitored between 2 temperature set points. When the lower one (16 °C) was reached, ventilation was stopped; when the higher one (16.8 °C) was reached, ventilation restarted. Power consumption, cheese mass loss and cheese quality were determined as comparison criteria. The use of TSV involved important reductions on ventilation time (48%), energy consumption (42%), cheese mass loss (0.9%) leading to a positive impact on the economy of the ripening process. Additionally, as shown by microbiological, physicochemical and sensory analyses, TSV neither had negative nor significant positive effects on cheese quality. Highlights: Temperature based Sequential Ventilation (TSV) was performed on a cheese ripening room. TSV reduced energy consumption (42%) and ventilation time (48%) of the ripening room. TSV allowed a reduction of the cheese mass loss (0.9%) increasing the cheese yield. No significant effect of TSV on fully ripened Graviera cheese quality was shown.